2002
DOI: 10.1046/j.1365-2133.2002.04606.x
|View full text |Cite
|
Sign up to set email alerts
|

Terbinafine (LamisilR) treatment of toenail onychomycosis in patients with insulin-dependent and non-insulin-dependent diabetes mellitus: a multicentre trial

Abstract: With excellent cure rates and a good tolerability profile, terbinafine should continue to be a drug of choice for the treatment of toenail onychomycosis in the rising number of NIDDM patients receiving multiple medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 26 publications
3
51
1
1
Order By: Relevance
“…9,16,23,[39][40][41][42][43][44] The target toenail mycological and complete cure rates for standard, continuous-dose terbinafine observed for our study, 71% and 41%, respectively, are similar to most previously reported studies using the same dose and duration of treatment. 23,24,40,[45][46][47][48][49][50][51][52] The target toenail mycological cure rate for pulse terbinafine observed for our study, 59%, is also similar to previous studies. 18,19,21 Because our participants were nearly all male, generalization of our results to women may be limited.…”
Section: Discussionsupporting
confidence: 90%
“…9,16,23,[39][40][41][42][43][44] The target toenail mycological and complete cure rates for standard, continuous-dose terbinafine observed for our study, 71% and 41%, respectively, are similar to most previously reported studies using the same dose and duration of treatment. 23,24,40,[45][46][47][48][49][50][51][52] The target toenail mycological cure rate for pulse terbinafine observed for our study, 59%, is also similar to previous studies. 18,19,21 Because our participants were nearly all male, generalization of our results to women may be limited.…”
Section: Discussionsupporting
confidence: 90%
“…With the administration of daily 250 mg doses, mycologic and clinical response rates observed in toenails ranged from 72% to 92% and 45% to 77%, respectively. [109][110][111][112][113] Notably, there was little difference in both clinical and mycological response rates whether patients were treated for 12, 18 or 24 weeks. 109,[111][112][113] Infections of the fi ngernail demonstrated comparable response rates ranging from 71% to 100%.…”
Section: Onychomycosismentioning
confidence: 99%
“…46,47 In a multicenter study, insulin-dependent (IDDM) and non-insulin-dependent (NIDDM) diabetes mellitus patients with distal-lateral toenail onychomycosis were treated with terbinafine (250 mg/day for 12 weeks). 48 Of diabetic patients, 37 had IDDM and 52 NIDDM. At week 48, mycological cure (negative microscopy and culture) was achieved in 73% of patients, clinical cure (100% clearing) in 57.3%, and complete cure (mycological cure plus clinical cure) in 48.3%.…”
Section: Hiv Patientsmentioning
confidence: 99%
“…At week 48, mycological cure (negative microscopy and culture) was achieved in 73% of patients, clinical cure (100% clearing) in 57.3%, and complete cure (mycological cure plus clinical cure) in 48.3%. 48 In a study containing 215 diabetic patients, ciclopirox nail lacquer solution 8% was applied for six months with efficacy evaluations at 3 and 6 months. 21 Physicians rated the efficacy of ciclopirox as good in 62% of patients after 6 months of treatment.…”
Section: Hiv Patientsmentioning
confidence: 99%